Pengaruh Suhu Air dan Lama Waktu Perendaman Beberapa Jenis Sayuran Daun pada Proses Crisping - SUPARTHA UTAMA, I MADE; AYU NOCIANITRI, KOMANG; RINA PRATIWI PUDJA, IDA AYU (AGRITROP, 2007)
The primary cause of wilting in leafy vegetables after harvesting is high intensity of transpiration processthrough natural openings (stomata, hidatoda and lenticels). The mechanism of closing and opening of those naturalopenings is affected by the temperature of the environment. Under high external temperature, the stomata tendto open and vice versa. It is possible to diffuse water into the produce to give a vigorous effect by controlling theexternal temperature and moisture. The process is normally called crisping. The aim of this experiment was tostudy the effectiveness of crisping in order to give vigorous and freshness effects to four different leafy vegetables,namely lettuce, kangkung, leeks and chinese cabbage compared to those without crisping. The crisping processwas involving the immersion of produce in three different water temperatures (30, 40 and 50oC) combined withdifferent lengths of immersion times (1, 3, 5 and 7 minutes) and continued by immediate movement of produce tolow temperature (5±2oC) and stored for 12 hrs before placing and displaying at the show case under temperatureof 10±2oC. Produce treated as controls were provided without immersion in the warm water and stored at roomtemperature, and other was also placed at the show case. The result shows that the effectiveness of crisping dependedupon the physical structure or morphology of the respective vegetables. In general, the water temperatures of 30 and40oC and combined with the lengths of immersion time of 1-3 minutes were effective to improve the freshness andvigorousness of lettuce and leeks, while 7 minutes immersion was effective for kangkung and Chinese cabbage.